Dual values-based organizational identification in MNC subsidiaries: A multilevel study - Smale, Adam; Björkman, Ingmar; Ehrnrooth, Mats; John, Sofia; Mäkelä, Kristiina; Sumelius, Jennie (Journal of International Business Studies, 2015)
Dual organizational identification – with both the whole corporation and the local subsidiary – is considered valuable for subsidiary employees, international assignees, and multinational corporations (MNCs). While extant research has examined antecedents of separate targets of identification, it has not fully addressed the challenge of identifying factors capable of supporting both simultaneously. This study examines the influence of individual- and organizational-level factors on the dual values-based identification of foreign subsidiary employees. Drawing on acculturation and organizational socialization theory, we test hypotheses on multilevel data from 793 managers and professionals in 90 foreign subsidiaries belonging to 11 Nordic MNCs. The results show that dual values-based identification is associated with acculturation and first-hand contact at the individual level, and a supportive social context for affective learning at the organizational level. Through its emphasis on higher-order elements that connect different parts of the MNC, rather than those that lead to the formation of in-groups and out-groups, the values-based approach to identification contributes to our understanding of dual identification in MNC subsidiaries, and represents a more positive treatment of cultural diversity. The findings have heightened practical relevance given the emphasis individuals are placing on values congruence in career choices and MNC efforts at instilling shared values.